Polyglycolic acid block copolymer and preparation method thereof

By melt polymerization in the presence of a catalyst, the polyglycolic acid block copolymer is directly obtained, which solves the problems of low preparation efficiency and poor uniformity in the prior art, and realizes the high-efficiency and uniformity of polyglycolic acid block copolymer Prepared with excellent mechanical properties.

CN119264392AActive Publication Date: 2025-01-07CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310820295.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-05
Publication Date
2025-01-07
Estimated Expiration
2043-07-05

AI Technical Summary

Technical Problem

The existing polyglycolic acid block copolymer preparation process is low efficiency and poor product uniformity, making it difficult to ensure good uniformity and mechanical properties.

Method used

In the presence of a catalyst, a mixture of glycolide and hydroxyl-containing polymer wires is melt polymerized to obtain block copolymers directly through a one-step method, and the structure of hydroxyl-polymer is flexibly regulated to control the structure of block copolymers as dimples. segment or triblock to ensure uniformity and mechanical properties.

Benefits of technology

The efficient preparation of polyglycolic acid block copolymer is achieved, and the product has good uniformity and mechanical properties, avoiding degradation caused by secondary heating, and reducing the preparation cost and time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264392A_ABST
    Figure CN119264392A_ABST
Patent Text Reader

Abstract

The invention relates to the field of polymer preparation, and discloses a polyglycolic acid block copolymer and a preparation method thereof. The preparation method comprises the step of performing melt polymerization on a mixture containing glycolide and hydroxyl-containing polymer wires in the presence of a catalyst. The hydroxyl-containing polymer wire rod is more uniform and accurate in feeding amount, a polyglycolic acid segmented copolymer product with good uniformity can be obtained, the molecular weight polydispersity coefficient of the polyglycolic acid segmented copolymer is small, and the hydroxyl-containing polymer wire rod has a practical application foundation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer preparation, and in particular to a polyglycolic acid block copolymer and a preparation method thereof. Background Art

[0002] Polyglycolic acid (PGA), also known as polyglycolide or polyglycolic acid, is the simplest linear aliphatic polyester. It is a completely biodegradable material with excellent biodegradability, biocompatibility, gas barrier properties and good mechanical strength. It has been used in biomedical materials and has good application prospects in barrier materials, downhole tools and disposable packaging bags. However, polyglycolic acid itself has a fast hydrolysis rate, resulting in a short shelf life and poor toughness at room temperature, so it needs to be modified by copolymerization and other means to broaden its practical application areas.

[0003] At present, there are two main preparation processes for polyglycolic acid block copolymers based on the principle: one is a two-step process, that is, first obtain polyglycolic acid or its oligomers, and then connect the blocks together through further polycondensation reaction between polyglycolic acid and other blocks, or through the reaction of hydroxyl groups in polyglycolic acid with active groups such as epoxy groups or isocyanate; the other is a one-step process, which directly uses polymers containing active groups such as hydroxyl groups to directly initiate the ring-opening polymerization of glycolide to obtain polyglycolic acid block copolymers. The two-step preparation process has low preparation efficiency and can only obtain uncontrolled multi-block copolymers, while the one-step preparation process is not only more efficient, but also can obtain a certain diblock or triblock copolymer by controlling the structure of the initiator polymer.

[0004] In the prior art, the preparation process of polyglycolic acid block copolymers can be divided into kettle type, tubular type, screw reaction extrusion type and multi-equipment combination type based on the equipment process; and starting from glycolide, when polyglycolic acid block copolymers are prepared by twin-screw reaction extrusion, direct mixing and feeding are generally adopted, or feeding is carried out after low-temperature prepolymerization in a kettle. Summary of the invention

[0005] The inventors have found that when a twin-screw reactive extruder is used to prepare a polyglycolic acid block copolymer, since glycolide is a powder, and general polymers are in the form of particles, especially polymers with a low glass transition temperature, when a polymer (such as a hydroxyl-containing polymer) is used as an initiator, it is impossible to mechanically crush the desired polymer into a powder form at room temperature. Therefore, it is difficult to accurately and stably feed the raw materials into the twin-screw extruder according to a certain ratio. In particular, when the polymer particle ratio is low or the overall output is low, even if separate feeders are used, it is difficult to ensure the accuracy and uniformity of the ratio of each component in the fed raw material, which leads to poor uniformity of the product. When the method of prepolymerizing at low temperature in the kettle and then feeding the raw materials is adopted, although the uniformity of each raw material is improved by melt prepolymerization, a higher prepolymerization temperature must be used for polymers with a higher melting point, which is not conducive to controlling the side reactions of polyglycolic acid. When the prepolymerization temperature is high, the obtained polyglycolic acid prepolymer has a high molecular weight and is easy to agglomerate and crystallize into a hard block, which is not conducive to the material transfer operation. In addition, due to the extra prepolymerization process, the process method has a high preparation cost and low efficiency.

[0006] The purpose of the present invention is to provide a polyglycolic acid block copolymer and a preparation method thereof to overcome the problems that the preparation process of the polyglycolic acid block copolymer in the prior art is low in efficiency and the product is difficult to ensure good uniformity.

[0007] Based on the existing process, there is a continuous demand for low-cost, fast and efficient preparation of polyglycolic acid block copolymers, and it is necessary to ensure that the obtained products have good uniformity. In a first aspect, the present invention provides a method for preparing polyglycolic acid block copolymers. The preparation method comprises: melt polymerizing a mixture containing glycolide and hydroxyl-containing polymer wires in the presence of a catalyst.

[0008] The second aspect of the present invention provides a polyglycolic acid block copolymer prepared by the preparation method described in the first aspect of the present invention.

[0009] Compared with the prior art, the preparation method of the present invention has at least the following advantages:

[0010] (1) The present invention uses a hydroxyl-containing polymer wire as an initiator to initiate the ring-opening polymerization of glycolide, and directly obtains a block copolymer in a one-step method. Compared with the preparation method of post-processing and modifying polyglycolic acid using isocyanate or epoxy compounds, the present method is simpler and more efficient, and avoids the degradation of polyglycolic acid caused by the secondary heating process;

[0011] (2) The polyglycolic acid block copolymer obtained by the post-processing modification method is uncontrollable and has a multi-block structure (generally the number of blocks is not less than 3), while the preparation method of the present invention can flexibly control the structure of the obtained block copolymer by changing the structure and amount of the hydroxyl-containing polymer, and the structure is determined to be a diblock or triblock copolymer (depending on the structure of the hydroxyl-containing polymer);

[0012] (3) The feed amount of the hydroxyl-containing polymer wire of the present invention is more uniform and accurate, and a polyglycolic acid block copolymer product with good uniformity can be obtained. In addition, the molecular weight polydispersity coefficient of the polyglycolic acid block copolymer is small, which has a basis for practical application. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 is a schematic diagram of a twin-screw extruder in some embodiments of the present invention;

[0014] Figure 2 This is the H-NMR spectrum of the polyglycolic acid block copolymer in Example 1 after purification by dissolution in hexafluoroisopropanol and precipitation in tetrahydrofuran.

[0015] Description of Reference Numerals

[0016] 1. Feeding port 2. Feeding port 3. Devolatilization port DETAILED DESCRIPTION

[0017] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0018] The first aspect of the present invention provides a method for preparing a polyglycolic acid block copolymer, the preparation method comprising:

[0019] The mixture containing glycolide and hydroxyl-containing polymer strands is melt polymerized in the presence of a catalyst.

[0020] In the present invention, a hydroxyl-containing polymer wire is used as an initiator to directly initiate the ring-opening polymerization of glycolide, and a polyglycolic acid block copolymer is directly obtained by a one-step method. Not only is the preparation method simple, but the specific type of the hydroxyl polymer wire can also be selected to flexibly control the polyglycolic acid block copolymer. The prepared polyglycolic acid block copolymer product has good uniformity and excellent mechanical properties.

[0021] According to the present invention, after melt polymerization, subsequent steps can be selected according to the desired morphology of the polyglycolic acid block copolymer, such as extrusion, cooling and pelletizing after melt polymerization.

[0022] According to the present invention, as long as the purpose of the present invention can be achieved, the amount of the hydroxyl-containing polymer wire is not particularly limited. In some embodiments, the amount of the hydroxyl-containing polymer wire is 5 to 50 parts by mass, for example, 5 parts by mass, 10 parts by mass, 12 parts by mass, 27 parts by mass, 22 parts by mass, 27 parts by mass, 30 parts by mass, 40 parts by mass or 50 parts by mass, and the range of any two of the above values, preferably 10 to 30 parts by mass. Using the above embodiment, the prepared polyglycolic acid block copolymer product has good uniformity, mechanical properties and a basis for practical application.

[0023] According to the present invention, in some embodiments, the hydroxyl-containing polymer wire is a single feed or multiple feeds. Using the above embodiments, the prepared polyglycolic acid block copolymer product has good uniformity, mechanical properties and a basis for practical application.

[0024] In the present invention, it can be understood that when a single feed is used, the hydroxyl-containing polymer wire is a single type of wire; and when multiple hydroxyl-containing polymer wires are used, the types of the multiple hydroxyl-containing polymer wires can be the same type or different types as needed.

[0025] According to the present invention, in some preferred embodiments, the hydroxyl-containing polymer wires are 1 to 3 feeds.

[0026] According to the present invention, in some embodiments, the diameter of the hydroxyl-containing polymer wire is 0.5 to 4.0 mm, for example, 0.5 mm, 0.8 mm, 1.0 mm, 1.1 mm, 1.3 mm, 1.7 mm, 2.0 mm, 2.5 mm, 2.6 mm, 3.0 mm, 3.5 mm or 4.0 mm, and a range consisting of any two of the above values, preferably 1.0 to 2.5 mm. Using the above embodiment, the polyglycolic acid block copolymer product prepared has good uniformity and a basis for practical application.

[0027] In the present invention, the diameter of the hydroxyl-containing polymer wire refers to the diameter of its cross section.

[0028] The length of the hydroxyl-containing polymer wire in the present invention is not particularly limited, as long as the weight and diameter of the hydroxyl-containing polymer wire are met. The length can be specifically reflected by its linear density, for example, the linear density is 0.78 to 8.84 g / m; when multiple hydroxyl-containing polymer wires are used, hydroxyl-containing polymer wires of the same length are generally selected.

[0029] In the present invention, the coefficient of variation of the diameter of the hydroxyl-containing polymer wire is no more than 10%, for example, 1%, 2.7%, 3.3%, 3.5%, 5%, 6%, 7%, 8.9% or 10%, preferably no more than 5%.

[0030] The coefficient of variation in the present invention is a statistic that measures the degree of variation of each observed value. The coefficient of variation = sample standard deviation / average value * 100%, and the sample standard deviation = sample variance Where x i is the ith data point, For example, the diameters of the wire at different lengths are 2.00mm, 1.96mm, 2.04mm, 1.95mm and 2.05mm, respectively. The mean and sample standard deviation are 2.00 and 0.05, respectively, which can be abbreviated as 2.00±0.05mm. The coefficient of variation is 0.05 / 2.00*100%=2.5%.

[0031] According to the present invention, it can be understood that the hydroxyl-containing polymer wire is a hydroxyl-containing polymer having a wire structure, and its composition is basically a hydroxyl-containing polymer. The specific type of the corresponding hydroxyl-containing polymer can be selected as needed. In some embodiments, the composition of the hydroxyl-containing polymer wire is selected from polybutylene adipate-terephthalate (PBAT), polybutylene succinate-terephthalate (PBST), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polybutylene succinate (PBS), polylactic acid (PLA), polycaprolactone (PCL), polycarbonate (PC), polyvinyl alcohol (PVA) and copolymers thereof, polyethylene glycol (PEG) and copolymers thereof, polypropylene oxide (PPO) and copolymers thereof, and polysaccharide polymers.

[0032] According to the present invention, based on consideration of biodegradability, in some preferred embodiments, the composition of the hydroxyl-containing polymer is selected from polybutylene adipate-terephthalate (PBAT) and / or polylactic acid (PLA).

[0033] According to the present invention, as long as the purpose of the present invention can be achieved, the molecular weight of the hydroxyl-containing polymer wire is not particularly limited. In some embodiments, the number average molecular weight of the hydroxyl-containing polymer wire is not less than 10000 g / mol, for example, 10000 g / mol, 20000 g / mol, 30000 g / mol, 40000 g / mol, 50000 g / mol, 70000 g / mol, 90000 g / mol, 120000 g / mol, 130000 g / mol or other ranges higher than 130000 g / mol, or a range consisting of any two of the above values, preferably not less than 30000 g / mol. Using the above embodiment, the prepared polyglycolic acid block copolymer product has good uniformity and a basis for practical application.

[0034] In the present invention, the number average molecular weight of the hydroxyl-containing polymer wire can be detected according to gel permeation chromatography (GPC). The specific detection method can adopt conventional detection parameters in the art. For example, but not limited to, the following method is used: the test instrument is a PL-GPC50 gel permeation chromatograph of Angilent, USA, and the processing software is GPCoffline. During the test, the mobile phase is hexafluoroisopropanol containing 5mmol / L sodium trifluoroacetate, the flow rate is 1mL / min, the column temperature is 40°C, the injection volume is 100μL, the standard sample is PMMA, and the sample concentration is 1mg / mL.

[0035] According to the present invention, as long as the purpose of the present invention can be achieved, the hydroxyl value of the hydroxyl-containing polymer wire is not particularly limited. In some embodiments, the hydroxyl value of the hydroxyl-containing polymer wire is not less than 0.1 mgKOH / g, for example, 0.1 mgKOH / g, 0.5 mgKOH / g, 1 mgKOH / g, 4.8 mgKOH / g, 20 mgKOH / g, 35.4 mgKOH / g, 40.2 mgKOH / g, 80 mgKOH / g, 100 mgKOH / g, 150 mgKOH / g, 200 mgKOH / g, 250 mgKOH / g or 300 mgKOH / g, and the range composed of any two of the above values. Using the above embodiment, the prepared polyglycolic acid block copolymer product has good uniformity, mechanical properties and a basis for practical application.

[0036] According to the present invention, too large a hydroxyl group may affect the molecular weight and processing performance. In some preferred embodiments, the hydroxyl value of the hydroxyl-containing polymer wire is 1 to 200 mgKOH / g.

[0037] According to the present invention, as long as the purpose of the present invention can be achieved, the acid value of the hydroxyl-containing polymer wire is not particularly limited. In some embodiments, the acid value of the hydroxyl-containing polymer wire is not greater than 10 mgKOH / g, for example, 10 mgKOH / g, 8 mgKOH / g, 4.2 mgKOH / g, 2.7 mgKOH / g, 2.1 mgKOH / g, 1 mgKOH / g or other ranges less than 1 mgKOH / g, preferably not greater than 5 mgKOH / g. Using the above embodiment, the prepared polyglycolic acid block copolymer product has good uniformity, mechanical properties and a basis for practical application.

[0038] In the present invention, the hydroxyl value and acid value of the hydroxyl-containing polymer are measured according to the national standard of polyether polyols (GB / T12008.3-2009 and GB / T 12008.5 / 2010), and the hydroxyl value of the hydroxyl-containing polymer is the corrected hydroxyl value OHVc excluding the influence of the acid value and the base value, and the unit is mgKOH / g.

[0039] According to the present invention, as long as the purpose of the present invention can be achieved, the source of the hydroxyl-containing polymer wire is not particularly limited, and can be obtained from the market, or prepared by corresponding hydroxyl polymer particles. In some embodiments, the preparation method of the hydroxyl-containing polymer wire comprises: a mixture of hydroxyl-containing polymer particles and optionally a processing aid is melt-compressed, extruded, cooled, and pulled and wound to obtain the hydroxyl polymer wire.

[0040] According to the present invention, "optionally a processing aid" means that a processing aid may be added or not. When a processing aid is added, those skilled in the art may select the type of processing aid according to the requirements of the present invention and the field. For example, the processing aid includes at least one of a catalyst, an antioxidant, an anti-hydrolysis agent and a dispersant.

[0041] According to the present invention, when adding a processing aid, those skilled in the art can select the amount according to the needs of the present invention and multiple processing aids in the field. For example, by mass, the amount of the antioxidant is 0.1 to 2 parts relative to 100 parts by mass of the hydroxyl-containing polymer particles; the amount of the anti-hydrolysis agent is 0.1 to 2 parts relative to 100 parts by mass of the hydroxyl-containing polymer particles; and the amount of the dispersant is 0.1 to 2 parts relative to 100 parts by mass of the hydroxyl-containing polymer particles.

[0042] According to the present invention, it can be understood that when the processing aid is a catalyst, the prepared hydroxyl-containing polymer wire contains a catalyst component. When the hydroxyl-containing polymer wire is used to prepare the corresponding polyglycolic acid block copolymer, the catalyst can be added or not as needed.

[0043] According to the present invention, as long as the purpose of the present invention can be achieved, the device for preparing the hydroxyl-containing polymer wire is not particularly limited, including but not limited to a screw extruder; and the type of the screw extruder is not particularly limited, for example, an SHG small batch 3D printing consumables testing machine (single screw, screw diameter 25 mm) and a Labtech parallel co-rotating twin-screw extruder (screw diameter: 20 mm, aspect ratio: 40) can be selected; and in order to monitor the diameter of the prepared hydroxyl-containing polymer wire, a laser diameter gauge or a photoelectric diameter gauge can be equipped on the testing machine.

[0044] According to the present invention, the feeding rate of the mixture of hydroxyl polymer particles and optional processing aids is not particularly limited, and mainly depends on the size and specific configuration of the screw, for example, 0.5-5 kg / h.

[0045] According to the present invention, as long as the purpose of the present invention can be achieved, the screw speed is not particularly limited when preparing the hydroxyl-containing polymer wire, for example, 15 to 30 rpm.

[0046] According to the present invention, as long as the purpose of the present invention can be achieved, the pulling speed of the winding when preparing the hydroxyl-containing polymer wire is not particularly limited, for example, 0.1 to 2 m / s.

[0047] In the present invention, those skilled in the art can select corresponding melt-compression conditions according to needs, for example, the melt-compression conditions include: a temperature of 125 to 155°C.

[0048] In the present invention, when preparing the hydroxyl-containing polymer wire, the cooling method is not particularly limited. For example, it can be cooled and shaped in a water bath at a certain temperature, and one or more traction rollers can be traction-wound at a certain rate. The present invention has no limitation on this, so it will not be elaborated.

[0049] According to the present invention, as long as the purpose of the present invention can be achieved, the amount of the catalyst is not particularly limited. In some embodiments, the amount of the catalyst is 0.005 to 1 part by mass, preferably 0.01 to 0.2 parts by mass, relative to 100 parts by mass of glycolide.

[0050] According to the present invention, as long as the purpose of the present invention can be achieved, the type of the catalyst is not particularly limited. In some embodiments, the catalyst is selected from a salt compound corresponding to at least one of transition metal elements, IIA group metal elements, IIIA group metal elements, IVA group metal elements, and VA group metal elements.

[0051] According to the present invention, in some embodiments, the catalyst includes: an organic guanidine catalyst.

[0052] According to the present invention, in some preferred embodiments, the catalyst is a salt compound corresponding to at least one of Sn, Bi, Mg, Al, Ca, Fe, Mn, Ti and Zn, preferably a Sn salt.

[0053] In the present invention, the mixture of glycolide-containing and hydroxyl-containing polymer strands refers to a mixture of glycolide, hydroxyl-containing polymer strands and other optional raw materials.

[0054] According to the present invention, in order to obtain different types of polyglycolic acid block copolymers, in some embodiments, the mixture also contains other comonomers (i.e., monomers other than glycolide), preferably, the other comonomers are selected from cyclic monomers that can initiate ring-opening polymerization through hydroxyl groups, and further preferably include one or more of lactide, glycolide, caprolactone and valerolactone.

[0055] According to the present invention, as long as the purpose of the present invention can be achieved, the amount of other comonomers is not particularly limited. In some embodiments, the amount of other comonomers is not more than 50 parts by mass, for example, 1 part by mass, 5 parts by mass, 10 parts by mass, 15 parts by mass, 20 parts by mass, 30 parts by mass, 40 parts by mass or 50 parts by mass, and a range consisting of any two of the above values, preferably 10 to 30 parts by mass.

[0056] According to the present invention, in order to further increase the stability of the prepared polyglycolic acid block copolymer, in some embodiments, the mixture further contains a stabilizing aid.

[0057] According to the present invention, as long as the purpose of the present invention can be achieved, the type of the stabilizing agent is not particularly limited, for example, it can be an antioxidant and / or an anti-hydrolysis agent.

[0058] According to the present invention, as long as the purpose of the present invention can be achieved, the amount of the stabilizing agent is not particularly limited. In some embodiments, the amount of the other additives is not more than 3 parts by mass, for example, 0.1 parts by mass, 0.3 parts by mass, 0.5 parts by mass, 0.8 parts by mass, 1.0 parts by mass, 1.2 parts by mass, 1.5 parts by mass, 2.0 parts by mass or 3.0 parts by mass, and a range consisting of any two of the above values, preferably 0.5 to 1.5 parts.

[0059] In the present invention, other comonomers and stabilizing agents are merely listed as other optional raw materials for preparing the polyglycolic acid block copolymer. Those skilled in the art may also add other raw materials as needed in combination with the present invention, for example, metal passivators, lubricants, antistatic agents, light stabilizers and brighteners may also be added.

[0060] According to the present invention, the specific selection of the antioxidant is not particularly limited. Examples of the antioxidants include BASF's antioxidants Irganox 1010 and Irganox 1076, antioxidant 1024, antioxidant 1098, antioxidant 1098, antioxidant 686, antioxidant 686 and antioxidant 626, etc. The above antioxidants can be used alone or in combination.

[0061] According to the present invention, the specific selection of the anti-hydrolysis agent is not particularly limited, for example, it is at least one of a carbodiimide compound, an oxazoline compound and an epoxy compound, preferably a carbodiimide compound. In some embodiments of the present invention, the anti-hydrolysis agent S9000 is used as an example to illustrate the advantages of the present invention, but the present invention is not limited to this.

[0062] According to the present invention, the dispersant is not particularly limited. In some embodiments of the present invention, white oil is used as an example to illustrate the advantages of the present invention, but the present invention is not limited thereto.

[0063] Depending on when other comonomers and / or stabilizing aids need to be added, the other comonomers and / or stabilizing aids can be first mixed with the hydroxyl-containing polymer wire and then mixed with glycolide to form a mixture for melt polymerization, or can be first mixed with glycolide and then mixed with the hydroxyl-containing polymer wire to form a mixture for melt polymerization; the above "mixing" can be carried out outside the polymerization equipment or in the polymerization equipment.

[0064] According to the present invention, in some embodiments, when the glass transition temperature of the hydroxyl-containing polymer wire is lower than or equal to room temperature, the hydroxyl-containing polymer wire is directly mixed with the glycolide-containing material to obtain the mixture and then melt polymerized. Using the above embodiment, the prepared polyglycolic acid block copolymer product has good uniformity, mechanical properties and a basis for practical application.

[0065] According to the present invention, in some embodiments, when the glass transition temperature of the hydroxyl-containing polymer wire is higher than room temperature, the hydroxyl-containing polymer wire is mixed with a glycolide-containing material under conditions higher than the glass transition temperature to obtain the mixture, and then melt-polymerized, preferably, the mixture is mixed with a glycolide-containing material under conditions at least 5°C higher than the glass transition temperature of the hydroxyl-containing polymer wire and lower than its melting point to obtain the mixture, and then melt-polymerized. Using the above embodiment, the prepared polyglycolic acid block copolymer product has good uniformity, mechanical properties and a basis for practical application.

[0066] In the present invention, room temperature refers to the temperature in the operating room at that time, which is generally 15-30°C.

[0067] According to the present invention, the conditions for the melt polymerization are not particularly limited as long as the purpose of the present invention can be achieved.

[0068] According to the present invention, in some preferred embodiments, the melt polymerization conditions include: a processing temperature of 100 to 250° C., for example, 100° C., 120° C., 150° C., 180° C., 200° C., 210° C., 220° C., 230° C., 240° C. or 250° C., and a range consisting of any two of the above values, preferably 200 to 240° C. Using the above embodiment, the polyglycolic acid block copolymer product prepared has good uniformity and a basis for practical application.

[0069] According to the present invention, in some embodiments, the conditions of the melt polymerization include: a reaction time of 1 to 20 minutes, for example, 1 minute, 2 minutes, 3 minutes, 4 minutes, 6 minutes, 8 minutes, 10 minutes, 12 minutes, 13 minutes, 15 minutes, 18 minutes or 20 minutes, and a range consisting of any two of the above values, preferably 2 to 8 minutes. Using the above embodiment, the prepared polyglycolic acid block copolymer product has good uniformity, mechanical properties and a basis for practical application.

[0070] According to the present invention, in some embodiments, the melt polymerization is carried out in a screw extruder, preferably in a twin-screw extruder. Using the above embodiment, compared with other preparation processes, the equipment and site investment is lower, the preparation process is continuous, and the preparation efficiency is higher.

[0071] In the present invention, the twin-screw extruder equipment used includes twin-screw extruders of different designs, such as HAAKE Eurolab16 desktop parallel co-rotating twin-screw extruder produced by Thermo Fisher in the United States, ZSK Mcc18 or ZSK 40 co-rotating parallel twin-screw extruders produced by Coperion in Germany, etc.

[0072] According to the present invention, in some preferred embodiments, the screw length-to-diameter ratio of the twin-screw extruder is 25-80, preferably 40-70.

[0073] According to the present invention, in some preferred embodiments, the screw speed of the twin-screw extruder is 5 to 300 rpm, preferably 40 to 150 rpm.

[0074] According to the present invention, it is understood that when a twin-screw extruder is used as the polymerization device, the amount of the hydroxyl-containing polymer wire can be adjusted by changing the wire diameter, the number of wires and the screw speed.

[0075] According to the present invention, when a twin-screw extruder is used as a polymerization device, the reaction time during melt polymerization is the residence time of the raw material in the twin-screw extruder, and the residence time can be measured by methods known in the art, such as but not limited to the following method: using black masterbatch as a marker, and taking the time from the black masterbatch entering the screw to the darkest color of the discharge material at the die as the residence time.

[0076] According to the present invention, it can be understood that, in some embodiments, when a twin-screw extruder is used as a polymerization device, the operation mode of "when the glass transition temperature of the hydroxyl-containing polymer wire is lower than or equal to room temperature, the hydroxyl-containing polymer wire is directly mixed with the glycolide-containing material to obtain the mixture and then melt-polymerized" can be: Figure 1 As shown, the raw material containing glycolide is added to the twin-screw extruder at a certain speed using a feeder; at the same time, the raw material containing the hydroxyl-containing polymer wire is fed into the twin-screw extruder from the feed port 1 (which is not heated and only serves as a feeder).

[0077] According to the present invention, it can be understood that, in some embodiments, when a twin-screw extruder is used as a polymerization device, the operation mode of "when the glass transition temperature of the hydroxyl-containing polymer wire is higher than room temperature, the hydroxyl-containing polymer wire is mixed with the glycolide-containing material under conditions higher than the glass transition temperature to obtain the mixture and then melt-polymerize" can be: Figure 1 As shown, a feeder is used to add a raw material containing glycolide to a twin-screw extruder at a certain speed; at the same time, a raw material containing a hydroxyl-containing polymer wire is fed into the twin-screw extruder from a feed port 2 (where the temperature set here is higher than the glass transition temperature of the hydroxyl-containing polymer wire).

[0078] According to the present invention, the feeding rate of the glycolide-containing raw material is not particularly limited, and mainly depends on the size and specific configuration of the screw, for example, it can be 0.1 to 4.0 kg / h, preferably 0.5 to 2.0 kg / h.

[0079] According to the present invention, it can be understood that other comonomers and / or stabilizing aids can be mixed with glycolide and then fed, and can also be mixed with the hydroxyl-containing polymer wire and then fed; in addition, when the hydroxyl-containing polymer wire does not contain a catalyst or the catalyst content is insufficient, the catalyst to be added can be mixed with glycolide and then fed, and can also be mixed with the hydroxyl-containing polymer wire and then fed.

[0080] The second aspect of the present invention provides a polyglycolic acid block copolymer prepared by the preparation method described in the first aspect of the present invention.

[0081] In the present invention, the polyglycolic acid block copolymer prepared by the preparation method of the present invention not only has good uniformity and mechanical properties, but also has a basis for practical application.

[0082] According to the present invention, in some embodiments, the molecular weight polydispersity coefficient of the polyglycolic acid block copolymer does not exceed 1.8, for example, 1, 1.1, 1.2, 1.4, 1.46, 1.54, 1.56, 1.59, 1.69, 1.62, 1.63, 1.7 or 1.8.

[0083] According to the present invention, in some embodiments, under the test conditions of 230°C / 2.16kg, the coefficient of variation of the melt mass flow rate of the glycolic acid block copolymer samples taken at different times in the same batch does not exceed 10%, for example, 1%, 2.7%, 2.9%, 3.1%, 3.5%, 3.7%, 4.1%, 5%, 6%, 7% or 10%, preferably not more than 5%.

[0084] According to the present invention, in some embodiments, the coefficients of variation of the tensile strength and elongation at break between different samples of the polyglycolic acid block copolymer are each no higher than 10%.

[0085] According to the present invention, in some embodiments, the structure of the polyglycolic acid block copolymer is a diblock copolymer as shown in formula (I) or a triblock copolymer as shown in formula (II):

[0086]

[0087]

[0088] Wherein m1, m2, n1 and n2 all represent the degree of polymerization, wherein n1 and n2 are each independently a positive integer not less than 30, and m1 and m2 are each independently a natural number; R1 represents the main chain structure of the hydroxyl-containing polymer after removing the terminal hydroxyl group (such as x, y represent the degree of polymerization), R2 represents the structural unit repeating segment provided by other comonomers (such as ).

[0089] According to the present invention, it is understood that the groups at both ends of the polyglycolic acid block copolymer are hydroxyl groups.

[0090] The present invention will be described in detail by way of examples. In the following examples and comparative examples, unless otherwise specified, all raw materials are commercially available, wherein: glycolide (GL) is purchased from Boli Biomaterial Co., Ltd., with a purity of ≥99.9%; stannous acid and tetrahydrofuran are purchased from Sinopharm Chemical Reagent Co., Ltd., with a purity of AR grade. Hexafluoroisopropanol was purchased from Shanghai MacLean Biochemical Technology Co., Ltd. with a purity of 99.5%; antioxidant 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate) was purchased from BASF (China) Co., Ltd., antioxidant 608 (bis(2,4-dicumylphenyl)pentaerythritol di(phosphite) ester) and carbodiimide anti-hydrolysis agent S9000 (poly[nitrilomethane tetranitro[2,4,6-tri(1-methylethyl)-1,3-phenylene) were purchased from Shanghai Puzhan Industrial Co., Ltd., white oil (mineral oil for hydraulic use) was purchased from SKALN Group, France, with a brand name of ISO VG46; polybutylene adipate-terephthalate (PBAT) was purchased from BASF (China) Co., Ltd. with a brand name of F-Blend-C1200; polylactic acid (PLA) was purchased from Zhejiang Hisun Biomaterials Co., Ltd. with the brand name REVODE 110.

[0091] H NMR spectrum ( 1 H-NMR) test: The test was carried out on a JNM-ECZ500R / S1 nuclear magnetic resonance spectrometer from JEOL, Japan; tetramethylsilane (TMS) was used as an internal standard, and deuterated trifluoroacetic acid was selected as a solvent.

[0092] Characterization of molecular weight and its distribution: The test was carried out on a PL-GPC50 gel permeation chromatograph produced by Angilent, USA, and the processing software was GPC offline. During the test, the mobile phase was hexafluoroisopropanol containing 5 mmol / L sodium trifluoroacetate, the flow rate was 1 mL / min, the column temperature was 40°C, the injection volume was 100 μL, the standard sample was PMMA, and the sample concentration was 1 mg / mL.

[0093] Melt flow rate measurement: The test was conducted on a CEAST MF20 melt flow rate tester from Instron, USA. The test temperature was 230°C, the load weight was 2.16 kg, and the preheating time was 4 minutes.

[0094] Injection molding processing method and tensile mechanical properties test: The samples were injection molded into 5A tensile specimens (thickness: 2mm) on a HAAKEMiniJet micro-injection molding machine according to GB / T 1040.2-2006. The barrel temperature and mold temperature were 230℃ and 50℃, respectively, the injection pressure and time were 400bar and 5s, respectively, and the holding pressure and time were 100bar and 10s, respectively. Then, the tensile test was carried out on a 3344 material testing machine of Instron Company of the United States, with a tensile rate of 50mm / min and a clamp spacing of 50mm. The number of specimens for each batch of samples was at least 5.

[0095] Example 1

[0096] Preparation of hydroxyl-containing polymer wire: Polybutylene adipate-terephthalate (PBAT), stannous octoate, antioxidant 110, antioxidant 608 and white oil were mixed in a mass ratio of 100:0.1:0.5:0.5:0.5, and then added to a SHG small batch 3D printing consumables testing machine (single screw, screw diameter 25 mm) at a feeding rate of 2 kg / h. After melt compression, it was extruded from the die. The set temperatures from the feed port to the die were 140°C, 140°C, and 150°C, respectively. ℃, 140℃, 130℃ and 130℃; the screw speed is 18.0rpm, followed by water bath cooling, traction and winding (traction speed is about 0.2m / s), the diameter of the obtained PBAT wire is 1.70±0.06mm (i.e., the coefficient of variation of the diameter is 3.5%), and the linear density is about 2.79g / m; after testing, the number average molecular weight of the wire is about 30,000 g / mol, the hydroxyl value (corrected) and the acid value are about 40.2mgKOH / g and 2.7mgKOH / g respectively;

[0097] Preparation of polyglycolic acid block copolymers: Figure 1As shown, glycolide, antioxidant 1010 and antioxidant 608 are mixed uniformly in a mass ratio of 100:0.5:0.5, and added to a HAAKE Eurolab16 desktop parallel co-rotating twin-screw extruder (screw diameter: 16 mm, aspect ratio: 40:1) from a feeder at a speed of 0.9 kg / h; at the same time, a hydroxyl-containing polymer wire with a diameter of 1.70 mm is fed into the twin-screw extruder from the feed port 1, and after melt polymerization, it is extruded, cooled and pelletized to obtain the polyglycolic acid block copolymer; the screw The rotation speed is 50rpm. The twin-screw extruder has 11 sections from the feeding port to the die, numbered 1 to 11, among which the first section (i.e., feeding port 1) only plays the role of adding materials and cannot be heated. The temperatures of sections 2 to 11 of the extruder are: 120°C, 180°C, 240°C, 240°C, 240°C, 240°C, 240°C, 230°C, 220°C and 210°C, respectively. The devolatilization port is in the 9th section with a residence time of 3min. It is estimated that, by mass, the amount of hydroxyl-containing polymer wire used is approximately 22 parts by mass relative to 100 parts by mass of glycolide.

[0098] A small amount of the obtained polyglycolic acid block copolymer is dissolved in hexafluoroisopropanol, and then a large amount of tetrahydrofuran is added to precipitate the polyglycolic acid block copolymer and remove the unreacted PBAT; most of the solvent is filtered out and then vacuum dried to obtain a purified polyglycolic acid block copolymer, and its structure is characterized by nuclear magnetic hydrogen spectrum. The solvent is deuterated trifluoroacetic acid. The nuclear magnetic hydrogen spectrum of the polyglycolic acid block copolymer obtained after hexafluoroisopropanol dissolution and tetrahydrofuran precipitation purification is as follows Figure 2 shown.

[0099] Figure 2 Among them, the single peak at a (chemical shift of about 11.6ppm) is the solvent peak, the single peak at b (chemical shift of about 8.3ppm) corresponds to the absorption peak of the benzene ring hydrogen in terephthalic acid in PBAT, the single peak at c (chemical shift of about 5.1ppm) corresponds to the absorption peak of methylene hydrogen in polyglycolic acid, the multiple peaks at d (chemical shift of about 4.3-4.7ppm) correspond to the absorption peak of methylene hydrogen near the carbonyl group in butanediol in PBAT, the single peak at e (chemical shift of about 2.6ppm) corresponds to the absorption peak of methylene hydrogen near the carbonyl group in adipic acid in PBAT, and the multiple peaks at f (chemical shift of about 1.8-2.2ppm) correspond to the absorption peak of the intermediate methylene hydrogen in adipic acid and butanediol in PBAT; therefore, by Figure 2It can be seen that the purified polyglycolic acid block copolymer still includes PBAT and PGA segment structures, indicating that the obtained product is different from a simple blend, and the two segments are connected together by chemical bonds. In addition, the characteristic peak integral area ratio obtained by nuclear magnetic resonance hydrogen spectrum combined with the raw material and product molecular weight obtained by GPC can be calculated that the actual proportion of PBAT in Example 1 is about 20wt%.

[0100] The number average molecular weight of the prepared polyglycolic acid block copolymer is 88530 g / mol, the weight average molecular weight is 138120 g / mol, and the molecular weight polydispersity index (PDI) is 1.56; after testing, under the conditions of 230°C / 2.16kg, the melt mass flow rate obtained by sampling at different times from the same batch is 43.1±1.6 g / 10min, that is, the coefficient of variation is 3.7%.

[0101] Example 2

[0102] Preparation of hydroxyl-containing polymer wire: The preparation method is similar to that of Example 1, except that: there is no stannous octoate, antioxidant 110, antioxidant 608 and white oil, no additional additives are added to the PBAT wire, and the set temperature from the feed port to the die direction is changed to 140°C, 140°C, 150°C, 150°C and 150°C in sequence; the diameter of the obtained hydroxyl-containing polymer wire is 1.30±0.10mm (ie, the coefficient of variation of the diameter is 7.7%), and the linear density is about 1.63g / m; after testing, the number average molecular weight of the hydroxyl-containing polymer wire is about 40,000 g / mol, and the hydroxyl value (corrected) and acid value are about 35.4mgKOH / g and 2.1mgKOH / g, respectively;

[0103] Preparation of polyglycolic acid block copolymer: The preparation method is similar to that of Example 1, except that glycolide, stannous octoate, antioxidant 1010 and antioxidant 608 are mixed uniformly in a mass ratio of 100:0.1:0.5:0.5 and then fed, and at the same time, the hydroxyl-containing polymer wire with a diameter of 1.30 mm in the two basic examples is fed into the twin-screw extruder from the feed port 1. It is estimated that the amount of hydroxyl-containing polymer wire is about 27 parts by mass relative to 100 parts by mass of glycolide.

[0104] The number average molecular weight of the prepared polyglycolic acid block copolymer is 76040 g / mol, the weight average molecular weight is 117050 g / mol, and the molecular weight polydispersity index (PDI) is 1.54; after testing, under the conditions of 230°C / 2.16kg, the melt mass flow rate obtained by sampling at different times from the same batch is 53.7±1.9 g / 10min, that is, the coefficient of variation is 3.5%.

[0105] Example 3

[0106] Preparation of hydroxyl-containing polymer wire: Figure 1 As shown, polylactic acid (PLA) is added to a Labtech parallel co-rotating twin-screw extruder (screw diameter: 20 mm, aspect ratio: 40) at a feeding rate of about 5 kg / h for melt compression and extrusion from a die. The feed port is not heated, and the set temperatures from feed port 2 to the die direction are 150°C, 180°C, 200°C, 200°C, 200°C, 200°C, 200°C, 200°C, 200°C, 200°C, and the screw speed is 150 rpm, followed by water bath cooling, traction and winding (traction speed is 1.2 m / s), and the diameter of the obtained hydroxyl-containing polymer wire is 1.10±0.03 mm (i.e., the coefficient of variation of the diameter is 2.7%), and the linear density is about 1.19 g / m; after testing, the number average molecular weight of the wire is about 130,000 g / mol, and the hydroxyl value (corrected) and acid value are about 4.8 mgKOH / g and 4.2 mgKOH / g, respectively;

[0107] Preparation of polyglycolic acid block copolymer: The preparation method is similar to that of Example 1, except that: the hydroxyl-containing polymer wire in this example is used, and the feeding position of the hydroxyl-containing polymer wire is feed port 2; the feeding rate of the mixture of glycolide, antioxidant 1010 and antioxidant 608 is 0.8 kg / h, and the screw speed is 100 rpm; it is estimated that, based on mass, the amount of hydroxyl-containing polymer wire used is approximately 12 parts by mass relative to 100 parts by mass of glycolide.

[0108] The number average molecular weight of the prepared polyglycolic acid block copolymer is 97180 g / mol, the weight average molecular weight is 164100 g / mol, and the molecular weight polydispersity index (PDI) is 1.69; after testing, under the conditions of 230°C / 2.16kg, the melt mass flow rate obtained by sampling at different times from the same batch is 39.3±1.2 g / 10min, that is, the coefficient of variation is 3.1%.

[0109] Example 4

[0110] The preparation process of the hydroxyl-containing polymer wire is the same as that of Example 2.

[0111] Preparation of polyglycolic acid block copolymer: According to the method of Example 2, the difference is that the number of wires fed is changed from 2 to 1, and lactide and anti-hydrolysis agent are additionally added to the powder, glycolide, lactide, stannous octoate, antioxidant 1010, antioxidant 608 and anti-hydrolysis agent S9000 are mixed uniformly in a mass ratio of 80:20:0.1:0.3:0.3:0.5 and then fed; it is estimated that, based on mass, the amount of hydroxyl-containing polymer wire used is approximately 14 parts by mass relative to 100 parts by mass of glycolide.

[0112] The number average molecular weight of the prepared polyglycolic acid block copolymer is 72740 g / mol, the weight average molecular weight is 115420 g / mol, and the molecular weight polydispersity index (PDI) is 1.59; after testing, under the conditions of 230°C / 2.16kg, the melt mass flow rate obtained by sampling at different times from the same batch is 63.2±2.4 g / 10min, that is, the coefficient of variation is 3.7%.

[0113] Example 5

[0114] Preparation of hydroxyl-containing polymer wire: According to the method of Example 2, except that: the feeding rate (to about 0.5 kg / h) and the screw speed (to 5 rpm) are reduced, and the obtained wire diameter is 0.90 ± 0.08 mm (i.e., the coefficient of variation of the diameter is 8.9%), and the linear density is about 0.78 g / m; after testing, the number average molecular weight of the hydroxyl-containing polymer wire is about 40,000 g / mol, and the hydroxyl value (corrected) and acid value are about 36.8 mgKOH / g and 2.3 mgKOH / g, respectively.

[0115] Preparation of polyglycolic acid block copolymer: The method of Example 2 is followed, except that the number of wires fed is changed from 2 to 1. It is estimated that, based on mass, the amount of hydroxyl-containing polymer wire used is about 6.5 parts by mass relative to 100 parts by mass of glycolide.

[0116] The number average molecular weight of the prepared polyglycolic acid block copolymer is 111250 g / mol, the weight average molecular weight is 179820 g / mol, and the molecular weight polydispersity index (PDI) is 1.62; after testing, under the conditions of 230°C / 2.16kg, the melt mass flow rate obtained by sampling at different times from the same batch is 36.7±1.5 g / 10min, that is, the coefficient of variation is 4.1%.

[0117] Example 6

[0118] Preparation of hydroxyl-containing polymer wire: According to the method of Example 3, the difference is that the feeding rate (about 3.3 kg / h) and the screw speed (30 rpm) are reduced, the traction speed (to 0.1 m / s) is reduced, and the obtained wire diameter is 3.00 ± 0.10 mm (i.e., the coefficient of variation of the diameter is 3.3%), the linear density is about 8.84 g / m, and the number average molecular weight of the hydroxyl-containing polymer wire is about 130,000 g / mol, and the hydroxyl value (corrected) and acid value are about 5.2 mgKOH / g and 6.1 mgKOH / g, respectively.

[0119] Preparation of polyglycolic acid block copolymer: The method of Example 3 is followed, except that the feeding rate of the glycolide-containing powder is changed to 1.5 kg / h, the screw speed is changed to 150 rpm, and it is estimated that, based on mass, the amount of hydroxyl-containing polymer wire used is approximately 48 parts by mass relative to 100 parts by mass of glycolide.

[0120] The number average molecular weight of the prepared polyglycolic acid block copolymer is 51670 g / mol, the weight average molecular weight is 75230 g / mol, and the molecular weight polydispersity index (PDI) is 1.46; after testing, under the conditions of 230°C / 2.16kg, the melt mass flow rate obtained by sampling at different times from the same batch is 143.4±4.2 g / 10min, that is, the coefficient of variation is 2.9%.

[0121] Example 7

[0122] The preparation process of the hydroxyl-containing polymer wire is the same as that of Example 2.

[0123] Preparation of polyglycolic acid block copolymer: The method of Example 2 is followed, except that the number of wires is changed from 2 to 4. It is estimated that, based on mass, the amount of hydroxyl-containing polymer wires used is about 54 parts by mass relative to 100 parts by mass of glycolide.

[0124] The number average molecular weight of the prepared polyglycolic acid block copolymer is 42870 g / mol, the weight average molecular weight is 69830 g / mol, and the molecular weight polydispersity index (PDI) is 1.63; after testing, under the conditions of 230°C / 2.16kg, the melt mass flow rate obtained by sampling at different times from the same batch is 188.3±5.1 g / 10min, that is, the coefficient of variation is 2.7%.

[0125] Comparative Example 1

[0126] Similar to Example 1, but polybutylene adipate terephthalate (PBAT) is directly blended with glycolide and other powders in the form of particles and then added to the screw: Figure 1 As shown, glycolide, stannous octoate, antioxidant 1010, antioxidant 608 and polybutylene adipate terephthalate (PBAT) particles are uniformly mixed in a mass ratio of 100:0.2:0.5:0.5:22, and added to a HAAKE Eurolab16 desktop parallel co-rotating twin-screw extruder (screw diameter: 16 mm, aspect ratio: 40:1) from a feeder at a speed of 1.1 kg / h. After melt polymerization, the extruder is extruded, cooled and pelletized to obtain the polyglycolic acid block copolymer.

[0127] The number average molecular weight of the prepared polyglycolic acid block copolymer is 79410 g / mol, the weight average molecular weight is 147240 g / mol, and the molecular weight polydispersity index (PDI) is 1.85; after testing, under the conditions of 230°C / 2.16kg, the melt mass flow rate obtained by sampling at different times from the same batch is 48.3±5.1 g / 10min, that is, the coefficient of variation is 10.6%.

[0128] Application Examples

[0129] Example 1 and Comparative Example 1 were injection molded into 5A type tensile test strips, and their tensile mechanical properties were tested. The results are shown in Table 1.

[0130] Table 1

[0131] Tensile strength(MPa) Elongation at break (%) Example 1 32±2 748±42 Example 2 30±2 781±36 Example 3 98±4 10±1 Example 4 57±3 480±28 Example 5 83±3 345±17 Example 6 84±4 11±1 Example 7 28±2 803±44 Comparative Example 1 22±5 615±117

[0132] As can be seen from Table 1, the polyglycolic acid block copolymer in the comparative example has obvious defects, the coefficient of variation of the mechanical properties is significantly greater than 10%, and there are problems of stress concentration and poor mechanical properties. The specific polyglycolic acid block copolymer in this embodiment has excellent mechanical properties and excellent mechanical properties.

[0133] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A method for preparing a polyglycolic acid block copolymer, characterized in that: The preparation method comprises: The mixture containing glycolide and hydroxyl-containing polymer strands is melt polymerized in the presence of a catalyst.

2. The preparation method according to claim 1, wherein In terms of mass, the amount of the hydroxyl-containing polymer wire is 5 to 50 parts by mass, preferably 10 to 30 parts by mass, relative to 100 parts by mass of glycolide; and / or The hydroxyl-containing polymer wire is fed as a single strand or multiple strands, preferably 1 to 3 strands. When multiple strands are fed, the types of the multiple hydroxyl-containing polymer wires are the same or different. The diameter of the hydroxyl-containing polymer wire is 0.5 to 4.0 mm, preferably 1.0 to 2.5 mm; and / or The coefficient of variation of the diameter of the hydroxyl-containing polymer wire is not more than 10%, preferably not more than 5%.

3. The preparation method according to claim 1 or 2, wherein The composition of the hydroxyl-containing polymer wire is selected from one or more of polybutylene adipate-terephthalate, polybutylene succinate-terephthalate, polyethylene terephthalate, polybutylene terephthalate, polybutylene succinate, polylactic acid, polycaprolactone, polycarbonate, polyvinyl alcohol and copolymers thereof, polyethylene glycol and copolymers thereof, polypropylene oxide and copolymers thereof and polysaccharide polymers, preferably polybutylene adipate-terephthalate and / or polylactic acid; and / or The number average molecular weight of the hydroxyl-containing polymer wire is not less than 10,000 g / mol, preferably not less than 30,000 g / mol; and / or, The hydroxyl value of the hydroxyl-containing polymer wire is not less than 0.1 mgKOH / g, preferably 1 to 200 mgKOH / g; and / or, The acid value of the hydroxyl-containing polymer wire is not greater than 10 mgKOH / g, preferably not greater than 5 mgKOH / g.

4. The preparation method according to any one of claims 1 to 3, wherein The preparation method of the hydroxyl-containing polymer wire comprises: melt-compressing, extruding, cooling, pulling and winding a mixture of hydroxyl-containing polymer particles and optionally a processing aid to obtain the hydroxyl polymer wire; Preferably, the processing aid comprises at least one of a catalyst, an antioxidant, an anti-hydrolysis agent and a dispersant.

5. The preparation method according to any one of claims 1 to 4, wherein In terms of mass, the amount of the catalyst used is 0.005 to 1 part by mass, preferably 0.01 to 0.2 parts by mass, relative to 100 parts by mass of glycolide; and / or The catalyst is selected from salt compounds corresponding to at least one of transition metal elements, IIA group metal elements, IIIA group metal elements, IVA group metal elements, and VA group metal elements, and / or organic guanidine catalysts; Preferably, the catalyst is a salt compound corresponding to at least one of Sn, Bi, Mg, Al, Ca, Fe, Mn, Ti and Zn, preferably a Sn salt.

6. The preparation method according to any one of claims 1 to 5, wherein The mixture further contains other comonomers, preferably the other comonomers are selected from cyclic monomers that can initiate ring-opening polymerization through hydroxyl groups, and further preferably include one or more of lactide, glycolide, caprolactone and valerolactone; Preferably, the amount of the other comonomer is not more than 50 parts by mass, preferably 10 to 30 parts by mass, relative to 100 parts by mass of glycolide; and / or The mixture further contains a stabilizing agent, preferably the stabilizing agent includes an antioxidant and / or an anti-hydrolysis agent; Preferably, the amount of the stabilizing agent used is no more than 3 parts by mass, preferably 0.5 to 1.5 parts by mass, relative to 100 parts by mass of glycolide.

7. The preparation method according to any one of claims 1 to 6, wherein: When the glass transition temperature of the hydroxyl-containing polymer wire is lower than or equal to room temperature, the hydroxyl-containing polymer wire is directly mixed with the glycolide-containing material to obtain the mixture and then melt polymerized; or, When the glass transition temperature of the hydroxyl-containing polymer wire is higher than room temperature, the hydroxyl-containing polymer wire is mixed with the glycolide-containing material under conditions higher than the glass transition temperature to obtain the mixture, and then melt-polymerized, preferably, the hydroxyl-containing polymer wire is mixed with the glycolide-containing material under conditions at least 5° C. higher than the glass transition temperature of the hydroxyl-containing polymer wire and lower than its melting point to obtain the mixture, and then melt-polymerized; and / or The conditions of the melt polymerization include: a processing temperature of 100 to 250° C., preferably 200 to 240° C. and / or a reaction time of 1 to 20 minutes, preferably 2 to 8 minutes.

8. The preparation method according to any one of claims 1 to 7, wherein The melt polymerization is carried out in a screw extruder, preferably in a twin-screw extruder; Preferably, The screw aspect ratio of the twin-screw extruder is 25 to 80, preferably 40 to 70; and / or The screw speed of the twin-screw extruder is 5 to 300 rpm, preferably 40 to 150 rpm.

9. A polyglycolic acid block copolymer prepared according to any one of claims 1 to 8; Preferably, the molecular weight polydispersity coefficient of the polyglycolic acid block copolymer is no more than 1.8; and / or Under the test conditions of 230° C. / 2.16 kg, the coefficient of variation of the melt mass flow rate of the glycolic acid block copolymer samples taken at different times in the same batch does not exceed 10%, preferably does not exceed 5%; and / or Under the test conditions of 230° C. / 2.16 kg, the melt mass flow rate of the glycolic acid block copolymer is 10 g / 10 min to 300 g / 10 min, preferably 20 g / 10 min to 60 g / 10 min; and / or The coefficients of variation of the tensile strength and elongation at break between different samples of the polyglycolic acid block copolymer are each no higher than 10%.

10. The polyglycolic acid block copolymer according to claim 9, wherein The structure of the polyglycolic acid block copolymer is a diblock copolymer as shown in formula (I) or a triblock copolymer as shown in formula (II): In the formula, m1, m2, n1 and n2 all represent the degree of polymerization, wherein n1 and n2 are each independently a positive integer not less than 30, and m1 and m2 are each independently a natural number; R1 represents the main chain structure of the hydroxyl-containing polymer after removing the terminal hydroxyl group, and R2 represents the structural unit repeating segment provided by other comonomers.

Citation Information

Patent Citations

  • Environment-friendly antibacterial foreign language translation machine material and preparation method thereof

    CN114381103A

  • Polyglycolic acid resin composition, film, preparation method and application

    CN115746514A

  • Polyglycolic acid biodegradable block copolyester and copolyester film thereof as well as preparation methods and applications of polyglycolic acid biodegradable block copolyester and copolyester film

    CN116003760A

  • Block copolymer of aliphatic-aromatic copolyester and polyglycolic acid as well as preparation method and application of block copolymer

    CN116003765A

  • Process and apparatus for continuously producing an elatomeric composition

    US20060108706A1